Surface water treatment by using biosand filter and hibiscus rosa sinensis leaves as heavy metal adsorption in Kangkar Senangar’s River, Johor - Hamidon, Nuramidah; Yahya, Siti Hajar; Mohd Sunar, Norshuhaila; Muhamad, Mimi Suliza; Harun, Hasnida; A. Hamid, Hazren; Ali, R. (Elsevier, 2020)
Water is our most precious natural resource. In this case study which is in the Kangkar Senangar Johor, many rural communities also drink surface water which does not meet the required quality standards, causing serious health problems. From the interview with the Village Head, they also didn’t have enough source of water supply. They only use groundwater as their water source to complete daily life task. Hibiscus Rosa Sinensis (HRS) leaves, as one of the well-known plant agricultural waste, a natural adsorbent, to remove iron (Fe) from aqueous solution by adsorption was investigated. In the present study, the potential adsorption of heavy metal was tested by different amount of adsorbent dosages as the factor affecting adsorption. Characterization of adsorbent was done by the means FTIR analysis to observe for the functional groups available on the adsorbent. Sorption was most efficient by using 0.60g of dosage with 200ml of water sample that taken from Kangkar Senangar’s river at contact time of 20 minutes. After adsorption, the water sample will be treating by Biosand Filtration (BSF). The function of BSF is to reduce the turbidity, changes of the colour of water sample, increase the pH and dissolved oxygen. The BSF will filter all the suspended matter in the water sample after adsorption.. Based on the result produced, the hypothesis was achieved. Overall, the highest adsorption of Fe by HRS leaves was 85.62% which when the 0.80g of adsorbent was added during week 2. In conclusion, the result showed that the average adsorption of Fe in each week achieved in a range of 70 to 80%. This proved that Hibiscus Rosa Sinensis leaves was an effective natural sorbent.